A comparative study of five laboratory tests for foeto-placental dysfunction in late pregnancy. Issue 4 (April 1973) - Watson, D.; Siddiqui, S. A.; Stafford, J. E. H.; Gibbard, S.; Hewitt, V.
Abstract : Five foeto-placental function tests were studied in parallel in normal and abnormal late pregnancies with a view to establishing which test or tests is most satisfactorily able to identify the mother whose foetus is in danger. A critical examination of the levels in blood serum of two enzymes, placental phosphatase isoenzyme and cystine aminopeptidase, the polypeptide hormone placental lactogen (chorionic somatomammotrophin), and the oestrogen oestriol-17β is described. A correlation was attempted beween clinical data and the results of the above laboratory analyses and also with the daily urine oestrogen output. The plasma and urine oestriol levels proved generally to be the more useful warning tests in late pregnancy, whilst the plasma cystine aminopeptidase was the least sensitive indicator of foeto-placental dysfunction.